Laughing to Learn: Exploring the Impact of Teacher Humor on Motivation and Speaking Skill Development in Pakistani EFL Classrooms - Sajid Iqbal (JELLL, 2025)
The present study investigates the role of teacher humor in enhancing learners’ motivation and speaking skill development in English as a Foreign Language (EFL) classrooms at the primary level in Pakistan. Recognizing that affective factors significantly influence second language acquisition, this research explores how humor, as a positive pedagogical strategy, contributes to student engagement, confidence, and communicative competence. Adopting a qualitative research design, data were collected through classroom observations and semi-structured interviews involving three teachers and forty Grade 5 students from a government primary school in Tehsil Lawa, District Chakwal. Thematic analysis of the data revealed that humor was used in multiple forms—verbal, nonverbal, and situational—to facilitate understanding, reduce anxiety, and sustain learners’ attention. The findings indicate that appropriate and contextually relevant humor not only fosters a relaxed and interactive classroom atmosphere but also enhances students’ willingness to participate in speaking tasks. Most students reported increased motivation, better retention of vocabulary, and improved confidence when humor was integrated into lessons. However, the study also cautions that excessive or misplaced humor can momentarily distract learners from instructional goals. Overall, the research concludes that humor, when purposefully and sensitively applied, serves as a powerful tool for creating a supportive and communicative environment conducive to language learning. The study recommends that teacher training programs incorporate humor-based strategies to strengthen classroom rapport and promote active speaking among young EFL learners in Pakistan.